Urgensi Pendidikan Pranikah dalam Internalisasi Nilai Ketaatan dan Pencegahan Nusyuz sebagai Upaya Mewujudkan Ketahanan Keluarga: The Urgency of Premarital Education in Internalizing the Value of Nusyuz Obedience and Prevention as an Effort to Realize Family Resilience - Ashwab Mahasin; Moh Noval Rikza (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The rising phenomenon of domestic conflicts, including nusyuz behavior, poses a serious challenge to modern Muslim family life. Nusyuz, which refers to a spouse's disobedience or failure to fulfill marital obligations, often stems from a lack of understanding regarding the rights and duties of husband and wife according to Islamic teachings. Premarital education serves as a crucial instrument in internalizing values of obedience, responsibility, and healthy communication within the household. This study aims to examine the urgency of premarital education as a preventive measure against nusyuz by emphasizing the internalization of Islamic values. The research employs a qualitative approach using library research methods, where data is collected from relevant primary and secondary sources, including classical Islamic jurisprudence texts (fiqh), academic journals, books on Islamic education, and policy documents from marriage institutions. The findings indicate that structured premarital education grounded in Islamic values can enhance prospective spouses’ awareness of the importance of religious obedience and their respective roles within the family. The internalization of obedience values through premarital education is also shown to strengthen the emotional and spiritual foundation of couples, thereby minimizing the potential for nusyuz. In conclusion, premarital education is not merely an administrative requirement before marriage, but an essential need in building a sakinah family that is free from destructive conflict.